(3GdeYGQLs - (3GdeMbb GdMdj , LYaQ Hf GdMSf Hf jMji Hf GdMSjf Hf SYjO GdgPdj, fLe GdOjf CHh GdbGSe,J (B676 (3g` s
(3ChdgG (B:s
(3hHYO Pdc aEf JcQQ ef LeGYI ef GdCUMGH s
(3BNQgG (B:s
(3hZjQ Pdc ef GdCMGOjK GdOGdI Ydi GdefY ef bJd GdeSde s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B123 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B137s
(3eUOQ GbJfGA GdCUd (B:s
(3BjI Gddg GdMcje GdYGeI (B- (3GdfLa (B(177) s
Keywords: (3CUhd Gdabgs